Self and Sexuality: Contemporary British Women Playwrights and the Problem of Sexual Identity - Carlson, Susan (Journal of Dramatic Theory and Criticism, 1989)
Self and Sexuality: Contemporary British Women Playwrights and the Problem of Sexual Identity